As autarcas portuguesas na imprensa nacional: análise à projeção mediática de mulheres detentoras de cargo político - Afonso, Amália Cunha (2020)
There is no doubt that access to politics is a difficult path for them, especially in local government. The goal of this article is to (1) understand how the woman holds political office, (2) as it is mentioned in the national press, more specifically, in Jornal de Noticias and Público. And by complementing interviews with the analysis of press content, we can verify from this work that women have, over time, occupied a weaker position in the social structure, both in the public and private dimensions. It is curious, after a few years in democracy, that the number of women in politics is still so small.